Density Functional Theory Mechanistic Study of Boron‐Catalyzed N‐Alkylation of Amines with Formic Acid: Formic Acid Activation by Silylation Reaction. Issue 6 (28th February 2018) - Du, Pan; Zhao, Jiyang
Abstract: New methodology for the alkylation of amines is an intriguing issue in both academia and industry. Recently, several groups reported the metal‐free B(C6 F5 )3 ‐catalyzed N‐alkylation of amines, but the mechanistic details of these important reactions are unclear. Herein, a computational study was performed to elucidate the mechanism of the N‐alkylation of amines with formic acid catalyzed by the Lewis acid B(C6 F5 )3 in the presence of hydrosilane. We found that the reaction started with the activation of formic acid through a novel model. Then, the high electrophilicity of the C center of the formic acid unit and the nucleophilic character of the amine resulted in a C−N coupling reaction. Finally, two sequential silyl‐group and H − transfer steps occurred to generate the final product. Upon comparing the reaction barrier and the hydrogenation of indole, our mechanism is more favorable than that proposed by the group of Yu and Fu. Abstract : 3‐2‐1 action ! HCO2 H is activated by two sequential silylation reactions, and this is accompanied by an increase in the electrophilicity of the C center of formic acid. The N‐alkylation of amines with activated formic acid under the catalysis of B(C6 F5 )3 is then examined. Upon comparing reaction barriers and the hydrogenation of indole, we propose a mechanism that is more favorable than that previously reported.